2004
DOI: 10.1093/jnci/djh022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Estrogen Receptor Destabilizing Compounds: Effects on Estrogen-Sensitive and Tamoxifen-Resistant Breast Cancer

Abstract: ZK-703 and ZK-253 are potent, long-term inhibitors of growth in both tamoxifen-sensitive and tamoxifen-resistant breast cancer models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 20 publications
4
56
0
1
Order By: Relevance
“…For instance, fulvestrant analogues ZK-703 and ZK-253 (Fig. 1D) were shown to inhibit growth of ER+ xenografts, including tamoxifen-resistant tumors, more efficiently than ICI 182,780; interestingly, compound ZK-253 demonstrated increased oral bioavailability in these models (Hoffmann et al . 2004).…”
Section: Serms Vs Serds: Two Separate Classes Of Antiestrogens?mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, fulvestrant analogues ZK-703 and ZK-253 (Fig. 1D) were shown to inhibit growth of ER+ xenografts, including tamoxifen-resistant tumors, more efficiently than ICI 182,780; interestingly, compound ZK-253 demonstrated increased oral bioavailability in these models (Hoffmann et al . 2004).…”
Section: Serms Vs Serds: Two Separate Classes Of Antiestrogens?mentioning
confidence: 99%
“…2006), introduction of a tertiary amine in the ICI 182,780 side chain was associated with improved efficacy of compounds ZK-703 and ZK-253 at preventing growth of mouse xenografts from estrogen-sensitive and tamoxifen-resistant breast cancer lines (Hoffmann et al . 2004).…”
Section: Molecular Determinants Of Antiestrogenicitymentioning
confidence: 99%
“…Two new pure oestrogen antagonists, ZK-703 and ZK-253, which destabilise the ER, have been investigated using the MCF-7 xenograft model. ZK-703 and ZK-253 were not only more effective than either tamoxifen or fulvestrant at inhibiting the growth of ER-positive xenografts, they also showed a highly potent activity in tamoxifen-resistant xenografts (Hoffmann et al 2004). Clinical studies with both of these agents are awaited with interest.…”
Section: Other Pure Oestrogen Antagonists In Developmentmentioning
confidence: 99%
“…The growth rates for the ZR-75-1 xenografts with 50.6 pg/ml of serum E 2 and the Br-10 xenografts with 22.9 pg/ml of serum E 2 were slow compared with the rates for MCF-7 xenografts, but, by using E 2 implants, tumor volumes were greater than 500 mm 3 after 40 days of treatment (Table I). To evaluate the antitumor activity and ER degradation of CH4893237 against human breast tumors with low serum E 2 , we first used the ZR-75-1 xenografts which have been reported to show partial tamoxifen resistance (9). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hoffmann et al introduced an orally available steroidal SERD, ZK-253, which showed antitumor activities against ER-positive human breast cancer xenografts in 2004 (9). Dardes et al reported that an orally available nonsteroidal SERD, GW5638, was efficacious against ER-positive human breast cancer and endometrial cancer xenografts in 2002 and 2007 (10,11).…”
Section: Introductionmentioning
confidence: 99%